An Overview of the Public Understanding of Islamic Banking in Mendahara Ilir - Akbar Marhafis, Muhammad; Daud; Haeran; Pitri, Alisyah; Kartika Devi, Erwina (Journal of Economics and Social Sciences (JESS), 2025)
This study aims to examine the level of public understanding of Islamic banking in Mendahara Ilir Village, Mendahara District, East Tanjung Jabung Regency, Jambi Province. Using a qualitative approach with a descriptive method, the study reveals that although the term "Islamic bank" is fairly well known among the community, understanding of the underlying principles, systems, and products remains very low and largely symbolic. This lack of Islamic financial literacy is not due to rejection of the Sharia system, but rather stems from limited access to information, inadequate educational efforts from Islamic financial institutions, and the low integration of Islamic economic content in religious activities. The study finds that awareness of Islamic identity has not yet aligned with technical understanding of Sharia contracts (akad). Other findings suggest that direct experience in using Islamic banking services can serve as an important bridge toward deeper understanding. The study recommends contextual and collaborative Islamic financial literacy strategies, involving religious leaders, local media, experiential training, and the strengthening of Islamic economic curricula in both formal and informal education. With such strategies, Islamic financial inclusion in remote areas like Mendahara Ilir can be significantly improved, thereby supporting fair, sustainable, and Islamically-aligned local economic development